Unifying work values: establishing a circular framework based on basic human values - Schneider, Jannick; Kern, Marcel; Lorenz, Timo (Frontiers in Psychology, 2025)
This paper addresses challenges in personal work value research, particularly the lack of theoretical and explanatory foundations. With a focus on lists of constructs and potential biases and blind spots in past work value conceptualizations, the diversity of instruments used to assess values in organizational settings has led to ambiguity and incomplete progress in the field. By integrating propositions from basic value research, this paper develops a comprehensive work value theory. The theory is based on the compatibility and conflict of underlying basic motivational goals in work contexts, as postulated by the theory of basic human values. We review past instruments from work value research to consider a broad range of constructs with the purpose of refining broader work value constructs and enhance their theoretical capabilities in organizational settings. To achieve that, we resolve definitional inconsistencies, enable a context-sensitive theorizing of values in a motivational circumplex and broaden the scope of work value constructs to cover personal and social-focused dimensions. The latter is discussed considering the fantasmatic logic of neoliberal ideology. The developed theoretical framework can guide future research on the role of work values for organizational behavior and organizational performance, as well as on the role of fit between personal and organizational values. The paper concludes by highlighting the need to empirically validate the proposed work value model across different cultures and organizational contexts.